KANDUNGAN PROTEIN DAN ZINC PADA NUGGET KERANG DARAH (Anadara Granusa) - Hendrayati Hendrayati; Alya Fajriani Risal; Sunarto Sunarto; Nursalim Nursalim; Adriyani Adam (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Background; Intake of protein and zinc in toddlers is very important to support growth and development. Blood clams (anadara granusa) are a good source of protein and zinc. Blood clam nuggets are the use of local food ingredients into high nutritional value foods that can overcome nutritional problems, especially lack of protein and zinc intake.Methods: Research Analysis of protein and zinc content in blood clam nuggets in various formulations is an experimental study with a completely randomized design with three substitution treatments for blood clams (Anadara Granusa) 0%, (F0) 30% (F1), 40% , (F2) and 50% (F3). Design Post Test Group with two repetitions (duplo), analysis of protein metode Kjedhal and zinc levels. using the Atomic Absorption Spectrophotometer (AAS) method.Results: The protein content in (F0) had the lowest protein content, 16.54 g/100 g, while the sample with the highest substitution of blood clams (Anadara Granusa) (F3) showed the highest protein content of 18.39 g/100 g. The addition of blood clams substitution can increase the zinc nugget content. It can be seen from the results of the analysis of the zinc content (F0) that the lowest zinc content is 0.6585 g/100 g, while the blood shellfish substitution (Anadara Granusa) is the highest (F4) which has the highest zinc content of 1.952 g/100.Conclusion: The protein and zinc content is directly proportional to the substitution of blood clams (Anadara Granusa) in blood clam nuggets, the greater the substitution of blood clams (Anadara Granusa) the higher the protein and zinc content.Suggestion: The processing of blood clams (Anadara Granusa) must be ensured correctly and properly to ensure food safety.